The challenges of the bovine parasity saddle complex – BPS (Research, Society and Development, 2021)
This article presents the main challenges of the Bovine Parasitic Tristeza (TPB) complex, based on a literary review on the subject. TPB is a complex of diseases caused by the protozoa Babesia bovis and Babesia bigemina combined with the bacterium Anaplasma marginale, which are transmitted by the vector Rhipicephalus (Boophilus) microplus (tick) to its bovine host, negatively impacting the bovine host. animal health and causing millions in losses to the rural economy, either in the fight and control of the parasite, or in expenses with medicines, according to data from the Ministry of Agriculture, Livestock and Supply (MAPA), and the IBGE. The main methods of control and treatment of diseases caused by B. bovis, B. bigemina and A. marginale, at present, are summarized in the fight against the vector with the application of chemical products, such as acaricides, to contaminated animals. However, the challenges of this method lie in the practice of sequentially and frequently applying these chemicals to the bovine population, which generally causes the configuration of multi-drug resistant ticks to the chemical agents. Several studies have shown small results with homeopathic treatments and pasture rotation, alternative treatments to combat the Rhipicephalus microplus parasite. In 2020, MAPA launched a guide with the Selective Bovine Treatment (TBS) methodology, whose objective is to monitor the contaminated bovine population case by case to carry out the animal selection process, so that sick animals are treated. To ensure success, the Selective Control Program for Bovine Ticks (PCSCB) is offered, created by the Federal University of Paraná.